DEVELOPMENT OF ENTREPRENEURIAL COMPETENCE AND ITS ROLE IN THE RECONSTRUCTION OF UKRAINE - Melnychenko, Olga (Educological discourse, 2022)
The article is devoted to the analysis of the European experience in the formation of entrepreneurial competence, which implies a strong connection with the economic and financial literacy of a person. The article emphasizes that entrepreneurial competence includes pronounced social, pedagogical and content aspects and has specific characteristics. The author analyzed the concepts of "entrepreneurship", "entrepreneurial initiative" and characterized the main features, components of entrepreneurial education. Based on the European experience, the author notes that the problem of the development of entrepreneurial education may be quite appropriate in the system of higher education, in universities in particular, given their scientific, technical and innovative potential. The author analyzed the main models of entrepreneurial education used in world and European practice. Particular attention in the article paid to the development of entrepreneurial competence in Ukraine and the need to popularize the ideas of environmental and socially oriented entrepreneurship.